2013
DOI: 10.1002/ppul.22750
|View full text |Cite
|
Sign up to set email alerts
|

Colistin inhalation monotherapy for ventilator-associated pneumonia ofAcinetobacter baumanniiin prematurity

Abstract: Aerosolized colistin may be used as monotherapy for VAP due to A. baumannii infection in pre-term infants. A larger controlled study is warranted to corroborate the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…8,9 recently, we reported that nebulized cmS was successful in the treatment of neonates with VaP caused by mDr A. baumannii. 2 Similar results have been described by celik et al 10 and Kang et al, 11 who successfully treated neonates and preterm infants with VaP because of mDr A. baumannii and P. aeruginosa. the dosage regimens reported in the literature vary from author to author and are chosen empirically.…”
supporting
confidence: 81%
“…8,9 recently, we reported that nebulized cmS was successful in the treatment of neonates with VaP caused by mDr A. baumannii. 2 Similar results have been described by celik et al 10 and Kang et al, 11 who successfully treated neonates and preterm infants with VaP because of mDr A. baumannii and P. aeruginosa. the dosage regimens reported in the literature vary from author to author and are chosen empirically.…”
supporting
confidence: 81%
“…Thus, at this point, the data are mixed regarding whether adding inhaled colistin to systemic therapy improves clinical cure. Importantly, several studies have reported favorable outcomes of patients with ventilator-associated pneumonia caused by highly resistant Gram-negative bacteria, including XDR A. baumannii, treated with monotherapy inhalational colistin without adjunctive systemic therapy (255,259,261,263). However, these results should be viewed cautiously, as cases were nonrandomized leading to a potential selection bias.…”
Section: Current Treatment Optionsmentioning
confidence: 57%
“…Furthermore, resistance has emerged during therapy, although with variable frequency depending on the case series (255,261,263).…”
Section: Current Treatment Optionsmentioning
confidence: 99%
“…8 Therefore, aerosolized CMS has become a reasonable choice for minimizing systemic exposure and optimizing the benefiterisk ratio of therapy. Aerosolized CMS has been used as a monotherapy 9,10 or as an adjuvant to intravenous antibiotics in XDRAB pneumonia. 5,11 Some hospitals in Taiwan have also employed aerosolized CMS for eradication of XDRAB as part of their infection control measures.…”
Section: Introductionmentioning
confidence: 99%